Strain-induced dimensional phase change of graphene-like boron nitride monolayers. (25th July 2018) - Peng, Qing
Abstract: We investigate the coupling between the electronic bandgap and mechanical loading of graphene-like boron nitride ( h -BN ) monolayers up to failure strains and beyond by means of first-principles calculations. We reveal that the kinks in the bandgap-strain curve are coincident with the ultimate tensile strains, indicating a phase change. When the armchair strain is beyond the ultimate tensile strain, h -BN fails with a phase transformation from 2D honeycomb to 1D chain structure, characterized by the 'V'-shape bandgap-strain curve. Large biaxial strains can break the 2D honeycomb structures into 0D individual atoms and the bandgap closes.